La lectoescritura en el desarrollo de las competencias comunicacionales de los estudiantes de séptimo grado de la Unidad Educativa Edmundo Cevallos Aguirre, Colaisaca-Calvas, 2023. - León Arboleda, Jessica Valeria (2023)
The research entitled “Integration of Literacy as a Catalyst for the Communication Competencies Development in Seventh-Grade Students: A Study at the Unidad Educativa Edmundo Cevallos Aguirre, Colaisaca-Calvas, 2023” focuses on analysing the impact of literacy on the communication skills of seventh grade students at the Unidad Educativa Edmundo Cevallos Aguirre. This research main objective is to determine the influence of a teaching guide on the development of the above- mentioned competencies. In order to address the problem in a specific context, this research utilised methods such as documentary review, structured surveys and diagnostic evaluation, through a descriptive, non-experimental approach. The mixed-approach methodology makes it possible to combine quantitative and qualitative elements, revealing the deficiency of optimal literacy skills among students, negatively affecting their oral expression and communication skills in general. However, the implementation of the methodological guide and teaching strategies evidences significant advances in the acquisition and mastery of these competencies. In conclusion, the “Methodological Guide for Learning Literacy” motivates students to develop their literacy skills, thus improving their communication skills and facilitating their continuous acquisition of knowledge throughout their lives. Therefore, essential to stress the importance of promoting the practice of literacy as an essential tool to enhance students’ oral expression and communication skills in general, contributing to their educational and personal development. Key words: Literacy, competencies, communicational strategies, methodological guide.